2017
DOI: 10.1136/gutjnl-2016-311685
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics ofHelicobacter pyloriinfection as a determinant of progression of gastric precancerous lesions: 16-year follow-up of an eradication trial

Abstract: Long-term exposure to infection was associated with progression of precancerous lesions. Individuals infected with with these lesions may benefit from eradication, particularly those with atrophic gastritis without IM. Incomplete-type IM may be a useful marker for the identification of individuals at higher risk for cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
128
1
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(149 citation statements)
references
References 36 publications
8
128
1
12
Order By: Relevance
“…Our results are significantly influenced by two trials: The study by Morgan et al[22] as the largest trial with 1463 PYs follow up, and the study by Mera et al[19] as the cohort with the longest follow-up time. The Mera study was the only cohort followed for more than 5 years; subjects with preneoplastic gastric lesions were enrolled from a geographically circumscribed region of Colombia, and thus, the results may not be generalizable to the remainder of Latin America.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Our results are significantly influenced by two trials: The study by Morgan et al[22] as the largest trial with 1463 PYs follow up, and the study by Mera et al[19] as the cohort with the longest follow-up time. The Mera study was the only cohort followed for more than 5 years; subjects with preneoplastic gastric lesions were enrolled from a geographically circumscribed region of Colombia, and thus, the results may not be generalizable to the remainder of Latin America.…”
Section: Discussionmentioning
confidence: 81%
“…The cumulative reinfection rate at the 5 and 7 year time points were 36.2 and 48.6 per 100 PYs, respectively. Recurrence rates from different countries were combined for the first 6 years, 12 and 16 years (only one study had follow-up beyond 5 years[19]). Recurrence rate were higher in the first six months and decreased afterwards.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 It is reported that approximately half of the global population is infected with H. pylori. [4][5][6] H. pylori eradication may reduce gastric inflammation, 7 prevent progression toward precancerous lesions, 8 and decrease the incidence of gastric cancer. [4][5][6] H. pylori eradication may reduce gastric inflammation, 7 prevent progression toward precancerous lesions, 8 and decrease the incidence of gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Atrophy, intestinal metaplasia and dysplasia are considered pre-malignant lesions. The severity of the atrophy and metaplasia is quantified by the OLGA/OLGIM system, and in the research setting by the Correa histopathology score [21]. …”
Section: Introductionmentioning
confidence: 99%